2008
DOI: 10.1007/s10661-008-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

Vertical gradients of mineral elements in Pinus sylvestris crown in alkalised soil

Abstract: Alkalisation of soil has been assumed to be the principal cause of changes in vertical gradients of nutrients in Pinus sylvestris crown. The long-term influence of alkaline dust pollution (pHH2O 12.3-12.6) emitted from a cement plant on the element composition of soil and needles of Scots pine in different canopy layers was studied. In the polluted area, the pH of soils was >7, and high amounts of Ca, K and Mg were measured in the upper layers of soil (0-30 cm), while the mobility and solubility of some contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…However, Alloway (1995) supposed that soil pH does not play such a major role in the uptake of Cd, while its interaction with several other elements may have an essential role in the uptake and translocation Cd in plants. As cement dust, soils and pines growing in the vicinity of the cement plant contain Ca in high concentrations (Mandre et al 2008;Mandre 2009;Ots 2002) it can be to hypothesised that Ca may decrease the uptake, accumulation and translocation of Cd in the crown of pine. The same opinion is held by Österås and Greger (2003), who in their research proved that Ca reduces the accumulation of Cd in tissues of Norway spruce.…”
Section: Discussionmentioning
confidence: 99%
“…However, Alloway (1995) supposed that soil pH does not play such a major role in the uptake of Cd, while its interaction with several other elements may have an essential role in the uptake and translocation Cd in plants. As cement dust, soils and pines growing in the vicinity of the cement plant contain Ca in high concentrations (Mandre et al 2008;Mandre 2009;Ots 2002) it can be to hypothesised that Ca may decrease the uptake, accumulation and translocation of Cd in the crown of pine. The same opinion is held by Österås and Greger (2003), who in their research proved that Ca reduces the accumulation of Cd in tissues of Norway spruce.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated dusting caused leaf and stem N of cotton to decrease (Li, 2005). Cement dust caused a decline in needle N content of Pinus sylvestris (Mandre, 2009) and N content of wheat (Pandey and Sanjeev, 1996).Cement dust also decreased the dry mass of Picea abies (Ots et al, 2011) and the biomass of tomato and radish (Magray et al, 2013). Dust on street trees decreased the amounts of photosynthetic pigments (Prusty et al, 2005;Prajapati and Tripathi, 2008).…”
Section: Growth Characteristics Were Affected By Dustmentioning
confidence: 99%
“…Most of the analyzed studies focused on nutrient concentrations in relation to biomass changes (Helmisaari 1992, Mandre 2009, Ots et al 2009. We aimed to analyze the needle N stocks in Scots pine stands to compare the impact of different treatments.…”
Section: Nutrient Allocationmentioning
confidence: 99%
“…A number of researchers attempted to explain the gradients of various causal factors, including light and temperature conditions, the water status of foliage (Pearcy & Sims 1994, Niinemets et al 2007, Gebauer et al 2011, photosynthetic capacity (Han et al 2003, Marcelis & Heuvelink 2007, needle anatomy (Richardson et al 2001, Lukjanova & Mandre 2009 or the concentration of carbohydrates (Mandre et al 1998). The nutrient uptake and translocation mechanisms in the canopies of conifers growing both naturally and under stress conditions have been explored in several studies (Helmisaari 1992, Finér 1994, Mandre 2009, Ots et al 2009). Helmisaari (1992 found that the dry mass per needle is low in the lower part of the crown, possibly as a result of changes caused by light.…”
mentioning
confidence: 99%
See 1 more Smart Citation